How does climate risk matter for corporate green innovation? Empirical evidence from heavy-polluting listed companies in China - Ling, Shixian; Gao, Hongfu (Frontiers in Energy Research, 2023)
Chinese heavy-polluting companies have been facing enormous challenges in responding to climate risk and energy transformation. This paper investigates the impact of climate risk on corporate green innovation in Chinese heavy-polluting listed companies from 2011 to 2020. The empirical results show that climate risk adversely affects green innovation in heavy-polluting companies, and this effect persists throughout a series of robustness and endogeneity tests. Climate risk may affect corporate green innovation through decreasing R&D investment, lowing resource allocation efficiency and increasing company risk. Climate risk has a greater negative impact on mid-western, state-owned and large-size heavy-polluting companies, but can be mitigated by the development of green finance, digital finance and marketization. These findings may help heavy-polluting companies fully utilize existing resources, policies, and channels for green innovation and mitigate climate risks.